Aktivitas Reduksi Merkuri pada Bakteri yang Diisolasi dari Air dan Sedimen di Sungai Musi - Titik Fadilah Amelia; Ace Baehaki; Herpandi Herpandi (Universitas Sriwijaya, 2016)
This study aims to isolate mercury resistant bacteria from water and sediment in Pulau Salah Nama which located on the River Musi Palembang, characterized mercury resistant bacteria growing at the highest concentration of HgCl2 and test the power of these bacteria in reducing mercury. The research was conducted from June 2015 until September 2015 using experimental methods laboris and descriptive data analysis. Reasecrh consissted of several stages, including sampling, bacterial isolation, characterization to determine the type of bacteria and mercury reducing power of bacteria. Isolation of bacteria produced 10 isolates. A1 was bacteria isolated from water and A2 was bacteria isolated from sediment. From 10 isolates selected 2 isolates of the higest concentration of HgCl2. Selected isolate A1 have the lowest mercury reduction power of 39.26% and selected isolate A2 have the highest mercury reduction power of 65.93%. In control medium without inoculant a decline in mercury concentration of 39.44%. Based on the characterization of the bacteria biochemical activity known A1 and A2 were Bacillus subtilis